Depraved heart : a Scarpetta novel - Cornwell, Patricia Daniels (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2015)
Working a suspicious death scene in Cambridge, Massachusetts, an emergency alert sounds on Dr. Kay Scarpetta's phone. A video link lands in her text messages and seems to be from her computer genius niece Lucy. But how can it be? It's clearly a surveillance film of Lucy taken almost twenty years ago.
Keywords: Scarpetta, Kay (Fictitious character) -- Fiction; Forensic pathologists -- Fiction; Women pathologists -- Fiction; Mystery fiction; Suspense fiction